Changes in the Transcriptome-Associated Co-Expression Profile of Embryonic External Ear Development After the BMP5 Gene Mutation. Issue 2 (4th March 2023) - Liu, Wei; Lin, Lin; Yang, Qinghua; Jin, Shengyang; Jiang, Haiyue
Abstract : This study aimed to perform an association analysis of the full transcriptome in Bmp5 short-ear mice during the development of the external ear in mouse embryos using advanced sequencing techniques. To understand the changes in gene regulation and expression of BMP5 gene mutations involved in the external ear embryonic development of mice, external ear tissues of mouse embryos developed to E15.5 and E17.5 were obtained using a BMP5 short-ear mouse model. The association analysis of the full transcriptome mainly involved the analysis of lncRNA and mRNA associations, the analysis of lncRNA and miRNA associations, the analysis of miRNA and mRNA associations, the analysis of circRNA and mRNA associations and circRNA, miRNA, and mRNA associations. The results showed that regulation of the full transcriptome is associated with external ear development in BMP5 short-ear mouse embryos, and some key regulatory changes in full transcriptome after BMP5 gene point mutation are different. This study will provide a new clue to investigate the mechanism underlying the regulation of mouse external ear development by the full transcriptome.